Bioinformatic analysis of a plakophilin-2-dependent transcription network: implications for the mechanisms of arrhythmogenic right ventricular cardiomyopathy in humans and in boxer dogs. (23rd November 2018) - Montnach, Jerome; Agullo-Pascual, Esperanza; Tadros, Rafik; Bezzina, Connie R; Delmar, Mario
Abstract: Aims: Previous studies in murine hearts and in cell systems have shown that modifications in the expression or sequence integrity of the desmosomal molecule plakophilin-2 (PKP2) can alter the downstream expression of transcripts necessary for the electrical and mechanical function of the heart. These findings have provided support to mechanistic hypotheses that seek to explain arrhythmogenic right ventricular cardiomyopathy (ARVC) in humans. However, the relation between PKP2 expression and the transcriptome of the human heart remains poorly explored. Furthermore, while a number of studies have documented the clinical similarity between familial ARVC in humans and inheritable ARVC in boxer dogs, there is a puzzling lack of convergence as to the possible genetic causes of disease in one species vs. the other. Methods and results: We implemented bioinformatics analysis tools to explore the relation between the PKP2-dependent murine and human transcriptomes. Our data suggest that genes involved in intracellular calcium regulation, and others involved in intercellular adhesion, form part of a co-ordinated gene network. We further identify PROX1 and PPARA (coding for the proteins Prox1 and PPAR-alpha, respectively) as transcription factors within the same network. Conclusion: On the basis our analysis, we hypothesize that the molecular cascades initiated by the seemingly unrelated genetic mutations in humans and in boxers actually converge downstream into a common pathway. This can explain the similarities in the clinical manifestation of ARVC in humans and in the boxer dogs.